The effect of grammatical guidance on the significance of the abrogated sentences in the first part of the Holy Quran: Semantic Grammar Study - Martini, Hala; Asaadi, Abdulkader (Al-Adab Journal, 2023)
The study aims to explain the significance of the grammatical structures that include the transcribers in the first part of the Holy Qur’an located in Surat Al-Baqara, by analyzing the grammatical structures that were mentioned in it and linking them to the meaning of the Qur’anic context and the general significance of the group of verses contained in it.To achieve this purpose, the researcher collected the verses that include transcribers in the first part of the Holy Qur’an, and worked on analyzing them and clarifying the indications that they added in the Qur’anic context, considering in this research the non-repetition of the indications.This study was divided into two parts: a theoretical part and another analytical application. The theoretical part deals with the abrogates in the Arabic language and seeks to reveal their significance in it. As for the applied analytical part, it analyzes the linguistic structures in which the abrogates were mentioned in the first part of the Holy Qur’an and shows their significance in the context. Quranic. Mentioning the most important findings at the end of the study.